''Budowanie mostów dla panów naukowców" - Kowalik, Stanisław (Wydział Prawa i Administracji UAM, 1996)
In his discussion of the jubilee achievement of the "Ruch Prawniczy, Ekonomiczny i Socjologiczny" quarterly, the author mainly focuses on three prominent Polish sociologists who had collaborated with the journal: F. Znaniecki, Cz. Znamierowski and T. Szczurkiewicz. He emphasizes the high degree of their methodological awareness and the impact they had on the factual calibre of "Ruch" and on the formation of Poznań scientific environment as a whole. With their belief in the necessity of scientific cooperation, in their work the three scholars marked out the paths for other scientific disciplines as well. Their sociological and interdisciplinary studies "built bridges" between particular fields of knowledge and proved inspirational for representatives of other branches of science. Finally, the author remarks on his own personal participation in editing the "Ruch", stressing the high prestige of the publication which is linked to the beginnings of Poznań University, and underlining the need for upholding its brilliant tradition.
Building bridges for scientists